2021
DOI: 10.1007/s12079-021-00648-w
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the tumor immune microenvironment by metformin

Abstract: Stimulating antitumor immunity is an attractive idea for suppressing tumors. CD4 + and CD8 + T cells as well as natural killer cells (NK) are the primary antitumor immune cells in the tumor microenvironment (TME). In contrast to these cells, regulatory T cells (Tregs), myeloid‐derived suppressor cells (MDSCs), cancer‐associated fibroblasts (CAFs), and tumor‐associated macrophages (TAMs) release several molecules to suppress antitumor immunity and stimulate cancer cell invasion and proliferation. Adjuvant treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 166 publications
0
19
0
Order By: Relevance
“…Preclinical studies have shown that in addition to increased insulin sensitivity and reduced gluconeogenesis, metformin inhibits cellular growth via regulation of AMP-activated protein kinase (AMPK) and liver kinase B1 (LKB1) pathways, leading to inhibition of the rapamycin (mTOR) pathway ( 19 21 ). There is growing data supporting that metformin also effects the TME and renders it more receptive for immunotherapy through the modulation of immune cells including T cells, natural killer (NK) cells, myeloid-derived suppressor cells (MDSCs) and tumor associated macrophages (TAMs) ( 20 , 22 24 ). However, metformin also inhibits PD-L1 expression on cancer cells through the action of AMPK ( 25 27 ) leading to concerns that concurrent metformin use may dampen the effect of ICIs.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have shown that in addition to increased insulin sensitivity and reduced gluconeogenesis, metformin inhibits cellular growth via regulation of AMP-activated protein kinase (AMPK) and liver kinase B1 (LKB1) pathways, leading to inhibition of the rapamycin (mTOR) pathway ( 19 21 ). There is growing data supporting that metformin also effects the TME and renders it more receptive for immunotherapy through the modulation of immune cells including T cells, natural killer (NK) cells, myeloid-derived suppressor cells (MDSCs) and tumor associated macrophages (TAMs) ( 20 , 22 24 ). However, metformin also inhibits PD-L1 expression on cancer cells through the action of AMPK ( 25 27 ) leading to concerns that concurrent metformin use may dampen the effect of ICIs.…”
Section: Introductionmentioning
confidence: 99%
“…By using such mechanisms, cancer cells are able to resist various types of drugs and anticancer agents such as ionizing radiation and hyperthermia 65 . The modulation of these mechanisms such as the induction of redox responses in the tumour, increasing the release of anticancer molecules and the induction of cell death pathways have all been considered to sensitize cancer cells to anticancer agents 66–68 . In this part, we discuss how apigenin may modulate anti‐tumour responses to increase the effects of anticancer agents.…”
Section: Modulation Of Cancer Response To Therapy By Apigeninmentioning
confidence: 99%
“…Diminished ATP levels in the cell leads to AMP-activated protein kinase (AMPK) activation, which inhibits the mammalian target of rapamycin (mTOR), thus inhibiting cell growth 23 . In addition to direct inhibition of tumor cells, metformin showed a potent immune modulator effect 24 . Metformin targets CD8 + cells in the TME; it maintains high cytotoxic T lymphocyte (CTL) activity in tumor tissues 25 .…”
Section: Introductionmentioning
confidence: 99%